2021
DOI: 10.3390/polym14010079
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Dynamics of Ring Chains on Two Asymmetric/Symmetric Chains in a Simple Slide-Ring Gel

Abstract: The sliding dynamics along two asymmetric/symmetric axial chains of ring chains linked by a linear chainis investigated using molecular dynamics (MD) simulations. A novel sub-diffusion behavior is observed for ring chains sliding along eithera fixed rod-like chain or fluctuating axial chain on asymmetric/symmetric axial chainsat the intermediate time range due to their strongly interplay between two ring chains. However, two ring chains slide in the normal diffusion at along time range because their sliding dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The conformational change between ring and chain has a decisive effect on the mechanical properties of glide ring gel. Reducing the covering area of the ring and increasing the length of the shaft chain can improve the toughness [ 45 , 46 ]. Because of the existence of the ring-chain, the selection of monomer is also limited, and the influence of conformation change on mechanical properties leads to more complex mechanical behavior.…”
Section: Mechanical Reinforcement Methodsmentioning
confidence: 99%
“…The conformational change between ring and chain has a decisive effect on the mechanical properties of glide ring gel. Reducing the covering area of the ring and increasing the length of the shaft chain can improve the toughness [ 45 , 46 ]. Because of the existence of the ring-chain, the selection of monomer is also limited, and the influence of conformation change on mechanical properties leads to more complex mechanical behavior.…”
Section: Mechanical Reinforcement Methodsmentioning
confidence: 99%
“…Understanding chain–chain conformation is fundamental to exploring the effects of ring‐chain slip. [ 56 ] Decreasing the ring coverage on the polymer chain and increasing the axial chain length leads to an increase in the sliding distance of the movable crosslinks and improves the toughness of SR gels. [ 57 ] A free‐energy function describing the mechanical toughening and slipping of topological knots is established to clarify the mechanism of collective entanglements in SR gels, which provides a basis for balancing deformability, rigidity, and toughness in gels.…”
Section: Enhancing Toughness Via Homogenous Hydrogel Networkmentioning
confidence: 99%
“…It was revealed that the temperature dependence of the segmental relaxation time for various glass-forming liquids can be well described by the DCN model. Wu et al proposed an original model for a system of mechanically interlocked molecules such as rotaxanes [ 2 ]. The sliding dynamics of rings along the two axial chain molecules (symmetric or asymmetric) were investigated via molecular dynamics simulations, where the rings are linked by a linear chain.…”
mentioning
confidence: 99%